A MITE insertion abolishes the AP3-3 self-maintenance regulatory loop in apetalous flowers of Nigella damascena. (13th December 2022) - Conde e Silva, Natalia; Leguilloux, Martine; Bellec, Arnaud; Rodde, Nathalie; Aubert, Juliette; Manicacci, Domenica; Damerval, Catherine; Berges, Helene; Deveaux, Yves
Abstract: MADS-box transcription factors are important regulators of floral organ identity through their binding to specific motifs, termed CArG, in the promoter of their target genes. Petal initiation and development depend on class A and B genes, but MADS-box genes of the APETALA3 (AP3) clade are key regulators of this process. In the early diverging eudicot Nigella damascena, an apetalous [T] morph is characterized by the lack of expression of the NdAP3-3 gene, with its expression being petal-specific in the wild-type [P] morph. All [T] morph plants are homozygous for an NdAP3-3 allele with a Miniature Inverted-repeat Transposable Element (MITE) insertion in the second intron of the gene. Here, we investigated to which extent the MITE insertion impairs regulation of the NdAP3-3 gene. We found that expression of NdAP3-3 is initiated in the [T] morph, but the MITE insertion prevents its positive self-maintenance by affecting the correct splicing of the mRNA. We also found specific CArG features in the promoter of the NdAP3-3 genes with petal-specific expression. However, they are not sufficient to drive expression only in petals of transgenic Arabidopsis, highlighting the existence of Nigella -specific cis / trans -acting factors in regulating AP3 paralogs. Abstract : A self-regulatory loop similar to that regulating euAP3 in core eudicots regulates AP3-3 gene expression in an early diverging eudicot, but distinct mechanisms control tissue specificities in Arabidopsis and Nigella.